Higher education in federal countries : a comparative study - Carnoy, Martin; Froumin, Isak D.; Leshukov, Oleg; Marginson, Simon, 1951- (Sage studies in higher education, 2018)
The first major study of what happens to higher education (universities and colleges) in federal systems.